2022
DOI: 10.48550/arxiv.2203.00993
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rpkiller: Threat Analysis from an RPKI Relying Party Perspective

Abstract: The Resource Public Key Infrastructure (RPKI) aims to secure internet routing by creating an infrastructure where resource holders can make attestations about their resources. RPKI Certificate Authorities issue these attestations and publish them at Publication Points. Relying Party software retrieves and processes the RPKI-related data from all publication points, validates the data and makes it available to routers so they can make secure routing decisions.In this work, we create a threat model for Relying P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Even worse, a malicious CA can create a large number of descendant RCs and operate numerous PPs to make RPs endlessly retrieve PPs, thus exhausting and paralyzing RPs. We find that Koen van Hove has demonstrated the feasibility of this attack by manipulating his PP (parent.rov.koenvanhove.nl) [55].…”
Section: B Data-driven Rpki Threat Analysismentioning
confidence: 88%
“…Even worse, a malicious CA can create a large number of descendant RCs and operate numerous PPs to make RPs endlessly retrieve PPs, thus exhausting and paralyzing RPs. We find that Koen van Hove has demonstrated the feasibility of this attack by manipulating his PP (parent.rov.koenvanhove.nl) [55].…”
Section: B Data-driven Rpki Threat Analysismentioning
confidence: 88%
“…Another recent work that performed similar research as [143] was done by van Hove et al [139]. Parts of this work were also published as an IETF draft [201].…”
Section: Attacks and Threat Modelsmentioning
confidence: 90%
“…The complexity of RPKI makes the creation of efficient, secure, bug-free, and RFC-compliant software implementations a complex task. Indeed, previous work found that due to missing limits on recursion depths, RP implementations were vulnerable to stalling attacks [18], [19], [20], [21], which was fixed by introducing thresholds to all the RP implementations. However, except for occasional bug reports, no systematic analysis of RPKI validation software has been performed to date.…”
Section: Introductionmentioning
confidence: 99%